Invisible faces and hidden stories : narratives of vulnerable populations and their caregivers - Obeng, Cecilia Sem; Obeng, Samuel Gyasi (Studies in public and applied anthropology, 2021)
"Dealing with narratives of vulnerable populations, this book looks at how they deal with dimensions of their social life, especially in regard to health. It reflects the socio-political ecologies like public hostility and stereotyping, neglect of their unique health needs, their courage to overcome adversity, and the love of family and healthcare providers in mitigating their problems. The narratives inform us about the dissimilarity between the way we speak, what we hear and how we act. American society likes to give the impression that it is listening to the plight of vulnerable populations, but the stories in this volume prove otherwise"--